What Makes a School a Happy School? Parents’ Perspectives - Patrícia Gramaxo; Filipa Seabra; Marta Abelha; Georg Dutschke (Education Sciences, 2023)
Well-being, equity, and inclusion are central aspects of happy schools. In this context, we aim to provide information to identify the characteristics of happy schools and Portuguese children’s level of happiness at school. In total, one thousand three hundred and ninety-nine parents of children from five to twenty years old participated in this study by answering a mostly open-ended questionnaire. They indicated their perceptions of how happy their children were at school, the moments they associated with individual happiness and unhappiness, and the characteristics of schools that they found conducive to promoting happiness. The findings show that parents value the relationships their children establish at school, teachers’ personal and professional skills, learning strategies, and the fact that students can be creative while learning valuable content. From the perspective of parents, unhappy schools are characterized by teachers with negative attitudes and attributes, bullying, an excessive workload, and consequent stress. Differences in terms of gender and age were not significant in this study. We found that levels of happiness at school decrease as students’ ages increase.